Malapetaka dan fitnah akhir zaman / Ibnu Katsir; Penerjemah, Muhammad Zaenal Arifin; Penyunting; Owen Putra dan Dendi Irfan - IBNU Katsir; MUHAMMAD Zaenal Arifin; OWEN Putra dan Dendi Irfan (Khatulistiwa Press, 2014)
xxiv, 410 hlm. ; 24 cm.